ICTs and labour productivity nexus in developing countries: evidence from panel estimation approach - Yong, Sze-Wei; Law, Siong-Hook; Ibrahim, Saifuzzaman; W. Mohamad, Wan Norhidayah (Universiti Malaysia Sarawak, 2024)
This study examines the impact of information and communication technologies (ICTs) on labour productivity in developing countries from 2000 to 2019, using the two-step System GMM estimation and dynamic panel quantile regression. The empirical results present new evidence on the moderating effect of ICTs with human capital, financial development and trade openness on labour productivity in developing countries. The interaction terms between ICTs and these three moderators show positive and statistically significant determinants of labour productivity. These three interaction terms have a greater influence on labour productivity than the impact of each variable assessed individually. The dynamic panel quantile regression results revealed that ICTs statistically significant to enhance labour productivity in lower and intermediate quantiles than in the highest quantiles in developing countries. This finding suggested that ICTs play an essential role in improving productivity at the lower and average labour productivity levels. This study can help policymakers develop a long-term strategy in terms of ICTs adoption and usage more intensively in developing countries as they strive to achieve the goals of industrial 4.0. © 2024, Universiti Malaysia Sarawak. All rights reserved.